Enhancing Access to Open Corpus Educational Content: Learning in the Wild - HEDERMAN, LUCY MARY; WADE, VINCENT PATRICK; LAWLESS, SEAMUS (My University, 2008)
The World Wide Web (WWW) provides access to a vast array of interconnected educational content on almost every subject imaginable. A great deal of this content is ideal for incorporation into personalised eLearning experiences. However the discovery, harvesting and incorporation of appropriate educational material have proven to be complex and arduous tasks. Traditional educational hypertext systems are based upon the generation of links and anchors between content objects [1]. However the dynamic incorporation of open corpus educational content in eLearning requires the generation of a relationship between educational concepts and the hypertext documents. One approach to create this overlay between concept and content is to use a Mindmap interface to allow learners to explore and associate hypertext content with knowledge maps of their own creation. This paper presents the Open Corpus Content Service (OCCS), a framework that uses the hypertext structure of the WWW to provide methods of educational content discovery and harvesting. The OCCS semantically examines linked content on both the WWW and in digital content repositories, and creates concept specific caches of content. The paper also introduces U-CREATe, a novel user-driven Mindmap interface for supporting the exploration and assembly of content cached by the OCCS, in a pedagogically meaningful manner. The combination of these systems benefits both the educator and learner, empowering the learner through ownership of the educational experience and allowing the educator to focus on the pedagogical design of educational offerings rather than content authoring.
PUBLISHED
Keywords: Computer Science and Engineering; Open Corpus Content Service (OCCS)